Gendhing-gendhing karawitan gaya Yogyakarta : wiled berdangga laras slendro hasil alih aksara naskah kuno / Dyan Anggraini Rais; penerjemah, R.M Palen Suwondo, R.M Suyamto; editor, Trustho, Bambang Sri Atmojo - RAIS, Dyan Anggraini; Palen Suwondo, R.M; Suyamto, R.M; Trustho, Bambang Sri Atmojo (Taman Budaya Yogyakarta, 2005)
xxxii, 700 hlm. ; 22 cm.